2020
DOI: 10.1186/s13756-020-00826-2
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant enterobacteriaceae in coastal water: an emerging threat

Abstract: Background The environmental role of carbapenemase-producing Enterobacteriaceae (CPE) acquisition and infection in human disease has been described but not thoroughly investigated. We aimed to assess the occurrence of CPE in nearshore aquatic bodies. Methods Enterobacteriaceae were cultured from coastal and estuary water near Netanya, Israel in June and July of 2018. Bacteria were identified by VITEK2® and their antimicrobial suscept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
11
1
3
Order By: Relevance
“…The Northeastern Pacific Ocean is a rich habitat that sustains a massive amount of phytoplankton, zooplankton, krill, and fish, all of which support a diverse and abundant community of more than 30 species of marine mammals [ 10 ]. Previous observations indicate that the marine environment may act as a reservoir of antimicrobial resistance genes [ 11 , 12 , 13 , 14 ]. Different mechanisms can lead to the presence of antimicrobial-resistant bacteria in the oceans: first, anthropogenic antimicrobial-containing runoff, challenging native bacteria to become resistant; second, coastal runoff of already resistant bacteria from terrestrial sources; and third—although less important in this context—antimicrobial production by marine microorganisms [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Northeastern Pacific Ocean is a rich habitat that sustains a massive amount of phytoplankton, zooplankton, krill, and fish, all of which support a diverse and abundant community of more than 30 species of marine mammals [ 10 ]. Previous observations indicate that the marine environment may act as a reservoir of antimicrobial resistance genes [ 11 , 12 , 13 , 14 ]. Different mechanisms can lead to the presence of antimicrobial-resistant bacteria in the oceans: first, anthropogenic antimicrobial-containing runoff, challenging native bacteria to become resistant; second, coastal runoff of already resistant bacteria from terrestrial sources; and third—although less important in this context—antimicrobial production by marine microorganisms [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…and E. coli carrying bla IMI-2 , were also isolated from river estuaries and beach water. Further molecular analysis and genome comparisons revealed the high similarity of these riverine and marine CRB from samples that were collected one month apart [77]. Thus, local sources, such as stormwaters and rivers, are an important source of CRB in the seawater and may have a significant effect on the composition of CRB in the marine environment (see Figure 1).…”
Section: Distribution Of Carbapenem Resistance In Marine Systemsmentioning
confidence: 98%
“…The dissemination of AR in seawater may be influenced by discharges from coastal runoff, aquaculture, polluted rivers, and WWTP effluents, which frequently contain resistant bacteria and resistant genes [72][73][74][75][76][77]. A study described that CRB communities in seawater and storm water samples did not differ significantly at the investigated sites, and the phylogenetic analysis showed that their CR isolates often belonged to the same species [25].…”
Section: Distribution Of Carbapenem Resistance In Marine Systemsmentioning
confidence: 99%
See 2 more Smart Citations